Parametric Optimization of NACA 4412 Airfoil in Ground Effect Using Full Factorial Design of Experiment - Shwe Yee Win (2022)
This investigation emphasizes the changes of the lift-to-drag ratio of an airfoil with the variation of ground clearance and angles of attack. Various ground clearances and angles of attack with a fixed speed of 30 m/s are applied to the NACA 4412 airfoil. Computational fluid dynamics (CFD) is used to calculate the aerodynamic coefficients acting on it. To study the influence of these two factors on the lift-to-drag ratio, 32 factorial design based on Design of Experiments (DOE) is utilized. A total of 9 numerical experiments were carried out with Ansys Fluent. When the angle of attack decreases, lift coefficient increases and drag coefficient decreases resulting in a high lift-to-drag ratio: also, the lower the ground clearance, the higher the lift-to-drag ratio. It shows the effectiveness of ground clearance and angle of attack. The analysis shows that either increasing ground clearance or using a higher angle of attack gives a decrement in the lift-to-drag ratio, but there is no interaction between them.